Polymer media for holographic data storage - Lau, Jason Yong Ching. (2010)
The ability of holographic data storage to record data in the volume of the media makes it one of the most promising technologies to replace current generation storage. It can store more than 1 Terabyte per disk with data transfer rates of up to 10 Gigabit per second. Dynamic range, which is determined by the refractive index change Δn during the recording, determines the final storage density. To achieve a higher Δn, high refractive index species can be easily and efficiently introduced into a low refractive photo-polymer media. In this project, the synthesis process of a sol-gel based photo-polymer holographic storage media was developed. Molecular level high refractive index species (HRIS), titanium (IV) isopropoxide was introduced into the media for the purpose of increasing the Δn. The synthesis process of sol-gel matrix with different pores was studied and the formation mechanism discussed. The effects of the sol-gel‟s pore size on the diffusivity of the monomers in the media were also studied holographically. It was found that smaller pore sizes slowed diffusivity, resulting in lower achievable diffraction efficiency. Larger pore size, synthesized with a GPTMS/TEOS molar ratio of 5 was able to increase the diffraction efficiency by 10 times. At the same time, the effect of HRIS concentration on the holographic recording performance was also studied. It was found that 30% of HRIS in the photo-polymer is the best concentration to achieve a maximum Δn of around 0.00113. Further increment of the amount of HRIS increased the light scattering level during holographic recording process. Due to the high scattering noise, the achieved refractive index change was also lower.